Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Pelanggan pada UD. Probo Sakti Kota Probolinggo Sebagai Pengusaha Penjualan Ayam Potong - Firdaus, M Amin; Haris, R Abdul; Koeshardjono, R Hery (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This research aims to examine the partial and simultaneous influence of service quality and price on customer satisfaction at UD. Probo Sakti Probolinggo City as an entrepreneur selling broiler chickens. This type of research uses quantitative descriptive with surveys and causal associative. The population was 112 people, with the sampling technique used in this study being simple random sampling. The data uses a questionnaire with data analysis techniques using validity tests, reliability tests, classical assumption tests, multiple linear tests, determinant coefficients, and hypothesis tests. The results show that service quality and price simultaneously and partially have a significant effect on customer satisfaction at UD. Probo Sakti Probolinggo City.